Castes of mind : colonialism and the making of modern India - Dirks, Nicholas B. (Princeton University Press, 2001)
This volume traces the caste system from the medieval kingdoms of southern India through early colonial archives to the 20th century. It surveys the rise of caste politics and how caste-based movements have threatened nationalist consensus.